Water production function of maize for Northeast Brazil - Sharma, Prem N.; Pereira, José Ribamar (Pesquisa Agropecuaria Brasileira, 2014)
The results of the randomized block experiment with four growth stages and four nitrogen levels to determine the water production function of maize (Zea mays L.) for Northeast Brazilian conditions are reported. The yield response factors as per Doorenbos and Kassam’s equation are found to vary drastically not only for different growth stages but also with different nitrogen levels and with different water levels. Thus, this equation is not a true representation of yield response to water. A modified linear equation with an intercept (K2) has been suggested. The coefficients of this modified equation (intercept K1 and the slope K2) are the modified yield response factors. These factors for maize have been developed here for all the four stages and for all the four nitrogen levels. The average highest water use efficiency of approximately 57.5 kg/ha-cm of water can be obtained but it shows no increase with increase in applied nitrogen up to 120 kg/ha. Finally crop coefficients (K c) have been calculated. The overall values of Kc are much below the FAO estimates for all nitrogen levels. All the above information developed here will help in better irrigation scheduling and better planning of supplemental irrigation projects in the Northeast Brazil.